Putative COVID- 19 Induction of Reward Deficiency Syndrome (RDS) and Associated Behavioral Addictions with Potential Concomitant Dopamine Depletion: Is COVID-19 Social Distancing a Double Edged Sword?. (21st September 2020) - Blum, Kenneth; Cadet, Jean Lud; Baron, David; Badgaiyan, Rajendra D.; Brewer, Raymond; Modestino, Edward J.; Gold, Mark S.
Abstract: Background: The overwhelming fatalities of the global COVID-19 Pandemic will have daunting epigenetic sequala that can translate into an array of mental health issues, including panic, phobia, health anxiety, sleep disturbances to dissociative like symptoms including suicide. Method: We searched PUBMED for articles listed using the search terms "COVID 19 Pandemic", COVID19 and genes, " "stress and COVID 19", Stress and Social distancing: Results: Long-term social distancing may be neurologically harmful, the consequence of epigenetic insults to the gene encoding the primary receptor for SARS-CoV2, and COVID 19. The gene is Angiotensin I Converting-Enzyme 2 (ACE2). According to the multi-experiment matrix (MEM), the gene exhibiting the most statistically significant co-expression link to ACE2 is Dopa Decarboxylase (DDC). DDC is a crucial enzyme that participates in the synthesis of both dopamine and serotonin. SARS-CoV2-induced downregulation of ACE2 expression might reduce dopamine and serotonin synthesis, causing hypodopaminergia. Discussion: Indeed, added to the known reduced dopamine function during periods of stress, including social distancing the consequence being both genetic and epigenetic vulnerability to all Reward Deficiency Syndrome (RDS) addictive behaviors. Stress seen in PTSD can generate downstream alterations in immune functions by reducing methylation levels of immune-related genes. Conclusion: Mitigation of these effects by identifying subjects at risk and promoting dopaminergic homeostasis to help regulate stress-relative hypodopaminergia, attenuate fears, and prevent subsequent unwanted drug and non-drug RDS type addictive behaviors seems prudent.